Politik Hukum Putusan Mahkamah Konstitusi Nomor : 46/PUU-VIII/2010 Tentang Status Anak di Luar Perkawinan Perspektif Siyasah Syar’iyyah - Jauhari Jauhari; Muhammad Burhan; Ulya Kencana (Simbur Cahaya, 2019)
Legal politics of the Constitutional Court Decision Number 46 / PUU-VIII / 2010 concerning the status of children outside of marriage is that Article 43 of Law Number 1 of 1974 which reads "Children born out of wedlock only have a civil relationship with their mother and mother's family" contrary to the 1945 Constitution. The legal politics of the Constitutional Court is based on the principle of "equality before the Law", namely the principle of "equality before the law". This principle is contained in the 1945 Constitution Article 28B paragraph (1) and (2) and Article 28D paragraph (1). According to the Court naturally, it is not possible for a pregnant woman without meeting between the ovum and spermatozoa either through sexual contact or through other means based on technological developments that cause fertilization. Therefore, it is incorrect and unjust when the law stipulates that a child born from a pregnancy due to sexual relations outside of marriage has only a relationship with the woman as his mother. Thus, the civil rights of children outside of marriage meant by the Constitutional Court's ruling are only material rights. Siyasah Syar'iyyah, in this case, is a review of the maqasid shari'ah that the aim is to protect and maintain the child's nasab (hifzuu nasl). So the study of sharia maqasid on the decision of the Constitutional Court Number 46 / PUU-VIII / 2010 is interpreted as civil rights to biological fathers only limited to material rights to children not the rights of the people and inheritance.